Inferior graft survival of hepatitis B core positive grafts is not influenced by post‐transplant hepatitis B infection in liver recipients—A 35‐year single‐center experience. (1st February 2016) - Brandl, Andreas; Stolzlechner, Philipp; Eschertzhuber, Stephan; Aigner, Felix; Weiss, Sascha; Vogel, Wolfgang; Krannich, Alexander; Neururer, Sabrina; Pratschke, Johann; Graziadei, Ivo; Öllinger, Robert
Summary: Nonoptimal liver grafts, and among them organs from anti‐HBc+ donors, are increasingly used for liver transplantation. In this retrospective study including 1065 adult liver transplantations performed between 1977 and 2012, we analyzed long‐term patient and graft survival and occurrence of HBV infection. A total of 52 (5.1%) patients received an anti‐HBc+ graft. The 10‐year graft and patient survival of these recipients were 50.9% and 59.0% compared to 72.0% and 76.5% ( P = 0.001; P = 0.004) of patients receiving anti‐HBc‐ grafts, respectively. Cox regression model showed that high urgency allocation ( P = 0.003), recipient age ( P = 0.027), anti‐HCV+ recipients ( P = 0.005), and anti‐HBc+ organs ( P = 0.048) are associated with decreased graft survival. Thirteen of 52 (25.0%) patients receiving anti‐HBc+ grafts developed post‐transplant HBV infection within a mean of 2.8 years. In this study, antiviral prophylaxis did not have significant impact on HBV infection, but long‐term survival ( P = 0.008). Development of post‐transplant HBV infection did not affect adjusted 10‐year graft survival (100% vs. 100%; P = 1). Anti‐HBc+ liver grafts can be transplanted with reasonable but inferior long‐term patient and graft survival. The inferior graft survival is not, however, related with post‐transplant HBV infection as long as early diagnosis and treatment take place.